Comparative Performance Analysis of Removal of Impulse Noise using Different Methods (International Journal of Engineering and Computer Science, 2017)
In this research paper we have introduced a comparative performance analysis of the removal of random valued impulse noise using different filters. Removal of random valued impulse noise in digital images with edge preservation is one of the challenging tasks in digital image processing. For elimination of noise from digital images plays a vital role. Effective detection of noisy pixel based on median value and an efficient algorithm for the estimation and replacement of noisy pixel has been carried out in different comparative methods in this paper. Here we have compare a different type of de-noising algorithms they are - Median filter (MF) [4], Centre weighted median filter (CWM) [6] [15], Progressive switching median filter (PSMF) [12], Signal dependent rank order median filter (SDROM) [9] [14], Adaptive center weighted median filter (ACWM) [10] [11], (ACWMF), Tristate median filter (TSM) [13. The presence of high performing detection stage for the detection noisy pixel makes the proposed method suitable in the case of high density random valued impulse noise. Here we have compare different method on the basis of PSNR and MSE values.